Ion channel accessory proteins: functions, physiology, and implications for pharmacology - Maher, Mike (Henry Stewart Talks, 2024)
Accessory proteins and ion channels, Glutamatergic synapses and AMPA receptors, TARPs and AMPA receptors, AMPA receptor subconductance states, Effects of TARP-γ8 selective modulators